The Effect of Individual Learning Programs on Self-Efficacy and Learning Motivation of Students With Special Needs at Inclusive Schools - Dwhy Dinda Sari (Universitas Negeri Malang, 2023)
The study's objectives were as follows: 1) to identify the difference between self-efficacy of students with special needs before (pretest) and after (post-test) being taught with the PPI; 2) to determine the difference in learning motivation of students with special needs before (pretest) and after (post-test) being taught with the PPI; and 3) to determine the effect of the Individual Learning Program in inclusive schools. The research method used is a pre-experimental design of the type One Group Pretest-Posttest Design. Further, non-probability sampling is used in this particular study with the sample consisted of ten students with special needs from Srikandi Elementary School. This study used a questionnaire to measure student self-efficacy and motivation as a non-test data collection technique. The results indicate a significant increase in self-efficacy and learning motivation among children with exceptional needs after being taught using the PPI. These findings suggest that the PPI is an effective instructional approach for enhancing the self-efficacy and learning motivation of children with exceptional needs. Furthermore, the value of Fcount is 101.871 larger than the value of Ftable 2.90, hence, Ha is acceptable. Individual learning programs can be shown to have an effect on the self-efficacy and learning motivation of children with special needs.